Proximate biochemical composition of some commercial marine fishes from Bay of Bengal, Bangladesh - Barua , P.; Pervez , M.A; Sarkar , D.; Sarker , S. (Mesopotamian Journal of Marine Sciences, 2022)
Fish is known to be one of the cheapest sources of animal protein and other essential nutrients required in human diets. The knowledge of proximate biochemical composition of fishery species is fundamentally important for: the application of different technological processes, the characteristics post-mortem of species, as an aspect of quality of raw material and giving an idea of sexual stage. The study was conducted to determine the proximate biochemical composition of four marine fishes of the Bay of Bengal, Bangladesh. The study fishes were Dasyatis americana, Dasyatis pastinaca, Dasyatis zugei and Gymnothorax favagineus. From the study, it was found that Dasyatis americana contains highest protein, fat and ash concentration while Dasyatis Pastinaca holds highest concentration of moisture and lowest value of protein and fat. On the other hand, Dasyatis zugei hold lowest concentration of moisture and ash. Proximate biochemical composition of all species showed that their percentage of protein and fat content are good and can be a food item in parallel to the bony fishes.